Do Shorter Product Cycles Induce Patent Thickets? - Patrick Frank Ernst Beschorner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
The traditional argument that shorter product cycles favor trade secret over patenting is reviewed. A game theoretic model provides an argument that shorter product cycles can induce firms to file more patent applications. The firms may be trapped in a prisoners' dilemma where all firms would jointly prefer to patent less and to not have a patent thicket. If firms start applying for patents on technologies which are not yet mature in order to cover ideas that may eventually turn successful, this may create a patent thicket. The transition into a situation where firms start patenting many ideas instead of single mature technologies is initiated and accelerated when network effects are present or patents exhibit a blocking property.
Keywords: L1; L2; O31; K2; 330; patent thicket; product cycles; licensing; network effects; Patent; Innovationswettbewerb; Gefangenendilemma; Network Externalities; Lizenzvergabe; Theorie; Theorie